Slow Poisoning? Interests, Emotions, and the Strength of the English NHS; Comment on "Who Killed the English National Health Service?" - Scott L. Greer (Kerman University of Medical Sciences, 2015)
Martin Powell makes the point that the death of the National Health Service (NHS) is constantly asserted without criteria. This article suggests that the NHS is many things, which makes criteria unstable. The alignment of interests in the structure of the NHS enables both overheated rhetoric and political strength, and that pluralization of provision might actually undermine that alignment over time.